A prospective and comparative study to evaluate the efficacy of oral pregabalin vs gabapentin combined with IV paracetamol as preemptive analgesic for post-operative pain in patients undergoing single level open lumbar spine decompression surgery in a tertiary health care center - Garg, Rohit N.; Vaje, Shweta Sonu; Patil, Hrishikesh; Bajaj, Sanket (International Journal of Research in Orthopaedics, 2023)
Background: Post-operative pain in spine surgery, whether neuropathic or nociceptive, presents a significant challenge for both surgeons and patients. Previous research has demonstrated the effectiveness of pre-operative oral gabapentinoids in reducing postoperative pain, extending the time to first rescue analgesia, and diminishing overall analgesic requirements. Methods: This study involved 120 patients undergoing lumbar discectomy for disc herniation. They were randomly assigned to receive pre-operative oral pregabalin, gabapentin, or a placebo, along with IV paracetamol as preemptive analgesia. The study assessed their efficacy through post-operative pain scores (VAS), and sedation scores (Ramsay sedation score) at various intervals, time to first rescue analgesia, and total analgesia consumption. Results: No significant differences were found in demographic variables, surgical levels, or duration among the groups. The placebo group had the shortest time to first rescue analgesia, while the pregabalin group showed the longest, with a notable difference. Across most time frames, the pregabalin group reported the lowest mean postoperative VAS scores, whereas the placebo group had the highest. Initial variations in sedation scores converged in later time frames, with the placebo group consistently recording the lowest scores. Total rescue analgesia (tramadol) in the initial 24 hours was highest in the placebo group, followed by the gabapentin group, and lowest in the pregabalin group, with no significant variance. Conclusions: This study affirms the superiority of pre-operative oral pregabalin with IV paracetamol. It effectively prolongs the time to first rescue analgesia and reduces overall analgesic consumption post-lumbar spine surgery, compared to pre-operative oral gabapentin with IV paracetamol.